Implementation of a Laboratory-Integrated Clinical Decision Support System for CKD Screening and Progression Detection in Primary Care - Jordi Tortosa-Carreres; Jonnathan Acevedo-Galvis; Mónica Piqueras; William Harold; Carmen Ramos; Jose Luis Górriz; Enrique Rodríguez-Borja; Francisco Brotons-Muntó; Eugenia Avelino-Hidalgo; Pablo Molina; Begoña Laíz-Marro (Biomedicines, 2026)
Background: CKD remains substantially underdiagnosed and inadequately monitored. Objectives: To evaluate whether a laboratory-integrated CDSS enables opportunistic CKD detection and longitudinal surveillance in Primary Care via automated KDIGO stratification and progression detection. Methods: We implemented a CDSS embedded within the laboratory information system at Hospital Universitari i Politècnic La Fe, a tertiary university hospital in València, Spain. A one-time baseline profile screened patients with diabetes, hypertension, or age 60–80 years without documented advanced CKD, while a follow-up profile targeted patients with advanced CKD or those previously assessed by baseline screening. Both profiles applied KDIGO risk stratification and automated detection of renal and albuminuric progression based on predefined criteria, classifying each patient into one of three action categories: no CKD or low-risk requiring no action; CKD requiring Primary Care monitoring; or CKD meeting criteria for automated nephrology referral. Missed opportunities for albuminuria monitoring and economic impact of the intervention were evaluated. Results: During a 4-month period, the CDSS processed 10,733 requests, of which 10,414 were evaluable. No further action was required in 8661 patients (83.2%), monitoring was recommended in 1591 (15.3%), and nephrology referral was triggered in 162 (1.6%). Among 82 patients with albuminuric progression, 39% had not undergone ACR testing for more than two years despite ongoing Primary Care contact. Following implementation, ACR testing increased by 15.0% compared with the previous year, resulting in an additional analytical cost of EUR 1550.54. Conclusions: The CDSS enabled systematic CKD detection and surveillance in Primary Care, identifying silent renal and albuminuric progression and supporting nephrology referral at minimal cost.